PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN SUPERVISI AKADEMIK TERHADAP MOTIVASI KERJA SERTA DAMPAKNYA PADA PENERAPAN PRINSIP PEDAGOGIS GURU SMK NEGERI KOTA TANGERANG - Kurniawati, Kurniawati; Darmojo, Hardjito S.; Jarnawi Afgani Dahlan (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2024)
This study aims to examine the influence of principal leadership on work motivation and the application of pedagogical principles of teachers at SMK Negeri Tangerang City, to examine the influence of academic supervision on work motivation and the application of pedagogical principles of teachers at SMK Negeri Tangerang City, to examine the influence of principal leadership and academic supervision together on work motivation and the application of pedagogical principles of teachers at SMK Negeri Tangerang City. The population in this study was 150 teachers with a sample of 100 teachers at SMKN Tangerang City. Data collection in this study used a questionnaire with a Likert scale. The research method used was a quantitative correlational method by conducting validity and reliability tests and reviewing references from previous journals. The results of the study showed that principal leadership directly had a positive but less strong effect on the motivation of teachers at SMKN 8 Tangerang City, academic supervision directly had a positive and significant effect on the application of pedagogical principles of teachers at SMKN Tangerang City, motivation directly had a positive but less significant effect on the pedagogical competence of teachers at SMKN 8 Tangerang City, principal leadership directly had a positive but less strong effect on the pedagogical competence of teachers at SMKN 8 Tangerang City, academic supervision directly had a positive and significant effect on the motivation of teachers at SMKN Tangerang City. Keywords: Principal leadership, academic supervision, work motivation, pedagogy.